Etika dalam Wraspati Tatwa - Istri Agung, I Gusti Agung (Institut Hindu Dharma Denpasar, 2019)
The Â tattwa is the absolute truth about the Divinity / Ida Sang Hyang Widhi Wasa. Tattwa is one source of the teachings of Hinduism, therefore it is inseparable from the Vedas. So by having each obtained from the description of Wrhaspati and Tattwa it can be concluded that Wrhaspati Tattwa means the teaching of the truth / essence of Dharma truth from Bhagawan Wraspati. This article aims to examine the ethical values contained in the teachings of Wrhaspati Tattwa. Based on studies that have been carried out it is known that Wrhaspati Tattwa teaches how to achieve deliverance or freedom from worldly ties through Sadanggayoga. The source of this teaching is the result of dialogue between Bhatara Siwa and Bhagawan. Ethics in waraspati tatwa is a teaching that contains samkya and yoga.